KEMAMPUAN MEMBACA TEKS BAHASA INGGRIS - Veronika Unun Pratiwi; Purwani Indri Astuti; Sari Handayani (Magister Scientiae, 2015)
The aim of this research is; (1) to know the ability of the students’ reading skills, and also to give and increase the students’ understanding in the reading text. ; 2) to know the difference of the students’ reading ability by repeating the reading text after their lecturer reads; 3) to know how far is the students non English to understand the English text by giving attention to the vocabulary of the texts to get the clear understanding. This research used descriptive qualitative researchthis research has done to get the clear information between one and the other, so the information from the source did not miss and change. Based on the data that has been collected through observation, interview, and documentation. Based on the research that has been done, it can be concluded that: (1) it has an improvement in students’ understanding the reading text; (2) there was also an interference from the team in teaching learning activies; 3) the non English students got a lot of vocabularies after doing this research.